2011
DOI: 10.1111/j.1365-3059.2011.02427.x
|View full text |Cite
|
Sign up to set email alerts
|

Dickeya species: an emerging problem for potato production in Europe

Abstract: Dickeya species (formerly Erwinia chrysanthemi) cause diseases on numerous crop and ornamental plants world‐wide. Dickeya spp. (probably D. dianthicola) were first reported on potato in the Netherlands in the 1970s and have since been detected in many other European countries. However, since 2004–5 a new pathogen, with the proposed name ‘D. solani’, has been spreading across Europe via trade in seed tubers and is causing increasing economic losses. Although disease symptoms are often indistinguishable from tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
456
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(489 citation statements)
references
References 48 publications
(119 reference statements)
14
456
0
6
Order By: Relevance
“…Dickeya chrysanthemi (formerly Erwinia chrysanthemi) is the causal agent of tuber soft rot and blackleg-like symptoms in many potato growing areas of the world (Young et al 1992, Toth et al 2011, Tsror et al 2012). However, our study found D. dadantii subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dickeya chrysanthemi (formerly Erwinia chrysanthemi) is the causal agent of tuber soft rot and blackleg-like symptoms in many potato growing areas of the world (Young et al 1992, Toth et al 2011, Tsror et al 2012). However, our study found D. dadantii subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Species belonging to this genus cause soft rot and blackleg on potato in temperate regions (Pèrombelon 2002, Toth et al 2011, Tsror et al 2012. The species structure of Dickeya is well defined, but not all species have been described and there is considerable overlap in host range.…”
Section: Introductionmentioning
confidence: 99%
“…are responsible for major losses in seed and ware potato production in Europe and worldwide (Pérombelon and Salmond 1995;Pérombelon 2002;Toth et al 2011). In Europe, the Dickeya spp.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2005, the presence of D. solani has been reported in potato in many European countries including The Netherlands, Finland, Poland, Germany, Belgium, France, United Kingdom and Sweden, as well as outside Europe, in Israel and Georgia. The species has become the predominant pathogen responsible for the blackleg incidences in Europe (Toth et al 2011;Tsror et al 2011;van der Wolf et al 2014). D. solani seems to be virulent in potato and possesses features allowing its easy spread and survival under the temperate climate in Europe (Czajkowski et al , 2012a.…”
Section: Introductionmentioning
confidence: 99%
“…in the epidemiology of potato blackleg and soft rot diseases in Europe has increased since 2009 when the new virulent Dickeya species named D. solani was described in potato for the first time (Slawiak et al 2009;van der Wolf et al 2014). Since then the pathogen has been found in association with potato plants and tubers in many European countries and in Israel and Georgia (for review see: Toth et al 2011). It is now generally accepted that D. solani causes severe rotting symptoms in potato in a range of environmental temperatures (Czajkowski et al 2016;Golanowska et al 2016), may survive in surface water for a relatively long time (Laurila et al 2008) and is capable of spreading and systemically infect the host under a wide range of natural conditions (Czajkowski et al 2012).…”
mentioning
confidence: 99%